ESKE, NATURLIGVIS! Om økopoesi og naturerotik i Eske K. Mathiesens økoerotiske lyrik - Gregersen, Martin; Skiveren, Tobias (Passage - Tidsskrift for litteratur og kritik, 2013)
Martin Gregersen & Tobias Skiveren: “ESKE, NATURALLY! On Ecopoetry and Eroticism of Nature in the Ecoerotic Poetry of Eske K. Mathiesen” Within Danish literary history, the works of Eske K. Mathiesen have long been flying under the radar. This neglect is possibly due to the fact that the close attention to nature and immediate environment displayed in these writings is generally conceived as anachronistic when contextualized within a hypermodern, technological, and globalized age, such as the one we are currently part of. However, the current climate crisis changes this. Looking through the optics of ecocritisicm, this article examines the view on nature in the lyrical work of Eske K. Mathiesen in relation to existing categories of literary history. By various readings of representative poems, this article argues that his work distinguishes itself by viewing nature through the eyes of both ecology and erotics. In other words, the lyrical work of Eske K. Mathiesen can be categorized as both eco- and erotic poetry, however, as this article suggests, it is more accurate to fuse the two and employ a concept of ecoerotic poetry.